Cystitis treatment with phytotherapy within the Rif, Northern Morocco - Noureddine Chaachouay; Hicham Orch; Lahcen Zidane (SpringerOpen, 2021)
Abstract Background Cystitis is often caused by a bacterial infection, which is the most widespread type among other urinary infections. This investigation was aimed to document detailed ethnobotanical information of medicinal plants used to heal cystitis problems because of their effective therapeutic properties. The study was carried in the Rif, from March 1, 2015, to April 15, 2017. Semi-structured direct interviews were carried with 657 interviewees to collect the indigenous therapeutic knowledge. Surveys included interviewed demographic profile and ethnomedicinal information. UR and MUV were applied in data analysis. Results A total of 60 plant species distributed in 51 genera and 31 families were commonly used by our interviewees in the therapy of cystitis. Apiaceae was designed by the highest number of species (7 species); Capparis spinosa L. was the medicinal plant most frequently prescribed by regional people. Leaves were the most commonly used plant part (41.5%), and the majority of herbal remedies were prepared from decoction (55 %). Conclusions This research is the first contribution to the ethnobotanical study of this region. It is suggested that the ingredients of natural plant species documented are being investigated to discover the therapeutic effects and mechanisms of action. Primary consideration must be paid to the preservation of medicinal species, comprehensive documentation of popular medicinal data, and biological validation of listed species. Graphical abstract